Surgical management of stress incontinence in women: The role of the family practitioner Part 1: Pre-operative issues - G. Rienhardt; P. de Jong (South African Family Practice)
The surgical management of stress incontinence in women should encompass a combined approach by the family practitioner and the specialist. This review, in two parts, discusses the place of the family practitioner in this process. The continence mechanism, pre-operative counselling, appropriate surgical procedures, post-operative complications and aftercare are all discussed, to enable the family practitioner to provide adequate support to the patient.